Pengaruh Komunikasi Interpersonal Dan Komitmen Organisasi Terhadap Kinerja Karyawan : (Studi pada salah satu perusahaan flagship di Kota Bandung) - Mutiara Octaviana; Soelaiman Sukmalana; Bulan Tati Fitria; Windi Matsuko Danasasmita (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
The study of human resources within the organization focuses on individual performance to achieve optimal results. Therefore, it is necessary to have effective communication and employees committed to the tasks assigned by the organization. This research departs from the problems in the field, which indicate that there are inadequate employee performance results that thoughts to cause by interpersonal communication and employee commitment. This study aims to determine the effect of interpersonal communication and organizational commitment on employee performance. The research method is a survey of employees who work at one of the flagship companies in Bandung with a sample of 35 employees. The results showed a significant effect of interpersonal communication and organizational commitment on employee performance. The study results recommend that companies have more interpersonal communication and employee commitment to achieve optimal performance.